Pet food safety: emerging bacterial hazards and implications for public health - Antunes, Patrícia (2024)
Bacterial hazards in pet food, especially in raw diets, are a current public health issue to both pets and humans. The most substantial body of evidence and consequent risk stems from food-borne pathogens such as Salmonella and bacteria resistant to last-resort antibiotics (e.g. colistin, third generation of cephalosporins, linezolid). State-of-the-art methods, particularly whole-genome sequencing, have been fundamental to link bacterial pathogens from pet food to human cases across different countries. While there are limited data on antimicrobial resistance, it is becoming increasingly evident that pet food can harbor multidrug-resistant bacteria, calling for increased vigilance within a One Health perspective, namely, by identifying transmission routes of pathogens and antimicrobial-resistant bacteria to pet food. A concerted action involving veterinarians, regulatory agencies, pet food industry, and other stakeholders is required to promote the awareness of pet food potential hazards to mitigate public health risks.